2018
DOI: 10.3892/ijmm.2018.3903
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin inhibits pristine-induced systemic lupus erythematosus in a murine model through CXCLs regulation

Abstract: Systemic lupus erythematosus (SLE) is associated with an increased risk of vascular complications. Lupus nephritis is a major manifestation of SLE in the clinic. Lupus nephritis is elevated by T helper type 17 (Th17) cells, the major pro-inflammatory T-cell subset, leading to autoimmunity modulation. Therapeutic treatments targeting leukocyte recruitment may be useful in attenuating vascular complications linked to SLE progression. 3,7,3',4'-Tetrahydroxyflavone (fisetin) is a flavonol and a member of the flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Furthermore, the oral administration of Naringenin avoided the development of collagen fibers compared with vehicle. It seems that Naringenin has the ability to protect against kidney injury, this effect has also been described previously for other flavonoids administered in lupus-prone mice models [35,36,52].…”
Section: Plos Onesupporting
confidence: 79%
See 3 more Smart Citations
“…Furthermore, the oral administration of Naringenin avoided the development of collagen fibers compared with vehicle. It seems that Naringenin has the ability to protect against kidney injury, this effect has also been described previously for other flavonoids administered in lupus-prone mice models [35,36,52].…”
Section: Plos Onesupporting
confidence: 79%
“…Proteinuria reflect the grade of lupus nephritis and constitutes one biomarker for disease monitoring [41]. Although it has been reported that the administration of flavonoids such as Baicalin or isoflavones for a short period reduces proteinuria [35,53], the long-term effect of Naringenin or other flavonoids in the urine protein level has been poorly evaluated [52]. Here, we demonstrated that the highest dose Naringenin decreased the proteinuria score from the first to the third month of treatment.…”
Section: Plos Onementioning
confidence: 59%
See 2 more Smart Citations
“…In order to induce inflammation in mice, the animals were intraperitoneally (i.p.) injected with 0.5 ml of pristane (2,6,10,14-tetramethylpentadecane (TMPD)) (Sigma, St. Louis, MO) as previously described 21 24 . PBS was administered to the control group.…”
Section: Methodsmentioning
confidence: 99%